2020
DOI: 10.1021/acssuschemeng.9b06263
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Variability in Lignocellulosic Biomass: A Review

Abstract: Feedstock variability is a significant barrier to the scale-up and commercialization of lignocellulosic biofuel technologies. Variability in feedstock characteristics and behavior creates numerous challenges to the biorefining industry by affecting continuous operation and biofuels yields. Currently, feedstock variability is understood and explained largely on the basis of chemical composition. Physical and mechanical properties and behavior of lignocellulosic feedstock in various unit operations, studied thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 266 publications
0
27
1
1
Order By: Relevance
“…For simplification, barks may be classified as softwood barks, hardwood barks, and cork-rich barks, and their chemical composition is compared with other lignocellulosic materials such as wood, agricultural wastes, and energy crops ( Table 2). Moisture content is an important parameter in the processing of lignocellulosic biomass, since it affects size reduction, drying, storage, transport, and processing of biomass [214]. Wood contains approximately 50% of moisture at harvest which is higher than that of agricultural wastes (20%) [214].…”
Section: Tree Barks and Other Lignocellulosic Materials: Chemical Difmentioning
confidence: 99%
See 1 more Smart Citation
“…For simplification, barks may be classified as softwood barks, hardwood barks, and cork-rich barks, and their chemical composition is compared with other lignocellulosic materials such as wood, agricultural wastes, and energy crops ( Table 2). Moisture content is an important parameter in the processing of lignocellulosic biomass, since it affects size reduction, drying, storage, transport, and processing of biomass [214]. Wood contains approximately 50% of moisture at harvest which is higher than that of agricultural wastes (20%) [214].…”
Section: Tree Barks and Other Lignocellulosic Materials: Chemical Difmentioning
confidence: 99%
“…Moisture content is an important parameter in the processing of lignocellulosic biomass, since it affects size reduction, drying, storage, transport, and processing of biomass [214]. Wood contains approximately 50% of moisture at harvest which is higher than that of agricultural wastes (20%) [214]. Moisture content of different lignocellulosic biomass types, including wood, agricultural wastes, and energy crops, measured by proximate analysis revealed that approximately 7-15% moisture is present in lignocellulosic materials at equilibrium conditions [215].…”
Section: Tree Barks and Other Lignocellulosic Materials: Chemical Difmentioning
confidence: 99%
“…3 Higher heating value (HHV) and lower heating value (LHV) accounting for moisture content. 4 The sample was not processed appropriately to allow for this calculation.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…A variety of recent review papers have described biomass feedstocks [4], pyrolysis of biomass [5,6], and biochar production and end use [7,8]. Given the diversity of feedstocks, conversion processes and postprocessing techniques for various end uses, biochar exhibits wide variation in its physical and chemical properties [9].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Image analysis techniques have been widely applied to measure lignocellulosic biomass features. Image analysis techniques for assessing crops and plant material involve extracting information from digital images of the lignocellulosic biomass (Yan et al, 2020). Unique features of the materials, such as shape, color, and surface texture, can be recognized.…”
Section: Introductionmentioning
confidence: 99%